2007
DOI: 10.29173/slw6806
|View full text |Cite
|
Sign up to set email alerts
|

Further Understanding of Collaboration: A Case Study of How It Works with Teachers and Librarians

Abstract: Collaboration between teachers and librarians is considered an essential element of school librarians' work. This case study examined a collaborative effort between teachers and librarians from diverse areas of expertise who collaborated in designing professional development workshops for a group of elementary school teachers and librarians. The purpose of the study was tofurther understand the process of teacher and librarian collaboration, and to evaluate the collaborative process using a proposed model of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…It shifts the focus away from the promotion of pedagogical renewal and exchange processes in favor of establishing a culture of collaboration and shared enrichment. Various studies included in the present systematic review and other studies beyond the scope of the review (Lofthouse & Thomas, 2017;Lu & Hallinger, 2018;Montiel-Overall, 2005) have shown that collaborative approaches take different forms depending on the prevailing context. Despite this, these contexts share the same common aim of school improvement.…”
Section: Discussionmentioning
confidence: 99%
“…It shifts the focus away from the promotion of pedagogical renewal and exchange processes in favor of establishing a culture of collaboration and shared enrichment. Various studies included in the present systematic review and other studies beyond the scope of the review (Lofthouse & Thomas, 2017;Lu & Hallinger, 2018;Montiel-Overall, 2005) have shown that collaborative approaches take different forms depending on the prevailing context. Despite this, these contexts share the same common aim of school improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Na literatura, os estudos indicam que a função educativa do bibliotecário torna-se mais evidente com o trabalho com os professores (Montiel-Overall, 2005, 2008Campello, 2009;2012).…”
Section: Mediação Da Informação Como Prática Do Trabalho Colaborativounclassified
“…Once upon a Time … Whilst our work practices differ owing to the requirements of our respective cohorts, the process of co-planning, co-implementing and co-evaluating this workshop has allowed us to find synergy in our approaches to facilitating student learning (Montiel-Overall, 2005). With our personal relationships already established through previous collaborative work, we felt that we could work together effectively (Pham, 2019) and explore new ways to address issues that we had noticed in relation to students' approaches to academic writing and use of sources in their academic work.…”
Section: Prologuementioning
confidence: 99%